Bentuk - Bentuk Perlindungan Anak Menurut Hukum Positif di Indonesia - Dedy Siswanto; Sri Budi Purwaningsih (Indonesian Journal of Law and Economics Review, 2017)
Child Abuse often encountered in families and communities, both in rural and urban areas. There are many problems in living in the family or in the community such as certain forms of criminal acts, such as murder, mistreatment, rape and theft on children which results in physical and psychological misery and suffering. Based on this, the purpose of this research is to find out the forms of child protection according to positive law in Indonesia. The research method used is normative juridical which tests the application of rules or norms in the positive law that apply by using the Statute Approach. The form of legal protection for children is given in a preventive and repressive manner. Preventive protection aims to take precautions before legal problems occur. While repressive legal protection is the protection provided by the law. The benefits of this research are that it can provide benefits to society, namely giving a comprehensive picture of the forms of child protection according to positive law in Indonesia.